Pengaruh Kapasitas Industri, Aktivitas Pelaku UMKM Tenun, Diversifikasi Produk Dan Promosi Terhadap Pendapatan Pelaku UMKM Tenun Dusun Samri Desa Poto Kecamatan Moyo Hilir Kabupaten Sumbawa - Sisi Heriani; Edi Irawan (Indonesia Economic Journal, 2026)
The purpose of this study is to examine how industrial capacity, weaving MSME actors' activities, product diversification, and promotion affect weaved fabric MSME actors in Samri Hamlet, Poto Village, Moyo Hilir District, Sumbawa Regency. Weaving MSMEs are one of the leading sectors in the research area with 115 business actors spread across Samri Hamlet, but this cultural potential has not been able to be optimally converted into sustainable economic benefits. This study uses a quantitative descriptive method with a survey approach through the distribution of questionnaires to 54 respondents determined using the Slovin formula. The data were analyzed using multiple linear regression analysis with SPSS software, after first testing the validity and reliability of the instrument as well as classical assumption tests which included normality, multicollinearity, heterokedasticity, and autocorrelation tests. The results showed that partially, industrial capacity (X1) did not have a significant effect on revenue (significance value 0.737 > 0.05), the activities of weaving MSME actors (X2) did not have a significant effect on revenue (significance value 0.929 > 0.05), product diversification (X3) did not have a significant effect on revenue (significance value 0.671 > 0.05), and promotion (X4) did not have a significant effect on revenue (significance value 0.206 > 0.05). Simultaneously, the results of the F test showed that the four independent variables had no significant effect on income (F calculated 0.481 < F table 2.561 with a significance of 0.750 > 0.05). The value of the determination coefficient (R²) of 0.038 or 3.8% indicates that independent variables are only able to explain 3.8% of income variations, while 96.2% are influenced by other factors such as access to training and mentoring, business networks, local wisdom, motivation of business actors, and demand and seasonality. This study concludes that weaving MSME actors in Samri Hamlet still rely on stable traditional production patterns with capacity building, activities, diversification, and promotion that are not optimal. The researcher is then advised to review the factors that determine the income of weaving MSMEs by considering the addition of more relevant variables according to the specific conditions of traditional weaving MSMEs in Samri Hamlet, Poto Village.